2021
DOI: 10.1021/acs.jpcc.0c09983
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Investigation into the Effects of Dissolved Organic Matter on H2O2 Activation over α-Fe2O3 (001) Surfaces

Abstract: The heterogeneous Fenton process is one of the efficient methods for wastewater treatment, and the effects of dissolved organic matter (DOM) when treating actual wastewaters are anticipated. However, the impact of DOM on H2O2 activation is not clearly understood yet. In this work, the α-Fe2O3 (001) surfaces are chosen as the model materials and the effects of the major functional groups in DOM on H2O2 activation are systematically investigated using density functional theory simulations. First, the adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…For example, Density Functional Theory (DFT) calculations show that the adsorption of H 2 O 2 is stronger on the deficient α-Fe 2 O 3 (001) surface than on the pristine surface. 116 The energy barrier of activation and the O–O bond length at the transition state are 3.65 kJ mol −1 and 1.60 Å for H 2 O 2 adsorbed on the α-Fe 2 O 3 surface with OVs, but 44.89 kJ mol −1 and 1.75 Å on the pristine α-Fe 2 O 3 surface. Analogously, introducing S vacancies (SVs) in Fe 3 S 4 (FS-100) creates strong peroxidase-like activity not available from SV-poor Fe 3 S 4 (FS-0), which can be attributed to the efficient adsorption of H 2 O 2 and its subsequent decomposition to HO˙ at the SVs of Fe 3 S 4 (Fig.…”
Section: Generation Of Reactive Oxygen Speciesmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, Density Functional Theory (DFT) calculations show that the adsorption of H 2 O 2 is stronger on the deficient α-Fe 2 O 3 (001) surface than on the pristine surface. 116 The energy barrier of activation and the O–O bond length at the transition state are 3.65 kJ mol −1 and 1.60 Å for H 2 O 2 adsorbed on the α-Fe 2 O 3 surface with OVs, but 44.89 kJ mol −1 and 1.75 Å on the pristine α-Fe 2 O 3 surface. Analogously, introducing S vacancies (SVs) in Fe 3 S 4 (FS-100) creates strong peroxidase-like activity not available from SV-poor Fe 3 S 4 (FS-0), which can be attributed to the efficient adsorption of H 2 O 2 and its subsequent decomposition to HO˙ at the SVs of Fe 3 S 4 (Fig.…”
Section: Generation Of Reactive Oxygen Speciesmentioning
confidence: 93%
“…For example, Density Functional Theory (DFT) calculations show that the adsorption of H 2 O 2 is stronger on the decient a-Fe 2 O 3 (001) surface than on the pristine surface. 116 The energy barrier of activation and the O-O bond length at the transition state are 3.65 kJ mol À1 and 1.60 Å for H 2 O 2 adsorbed on the a-Fe 2 O 3 surface with OVs, but 44.89 kJ mol À1 and 1.75…”
Section: àmentioning
confidence: 95%
“…10 Gong et al exploited four Fe active sites on the surface of α-Fe 2 O 3 (001) to probe the impact of various activation methods and dissolved organic substances (DOM) on the energy barriers of H 2 O 2 activation to *OH (44.89 kJ/mol). 11 Li et al explored the dissociation of H 2 O 2 on hexagonal boron nitride and obtained seven possible species, among which the energy barrier of H 2 O 2 activation to *OH was 86.6 kcal/mol. 12 However, the above-mentioned oxidants have insufficient catalytic activity for H 2 O 2 and poor selective stability due to their many active sites and complex activation mechanisms, posing a major obstacle to the large-scale application of advanced oxidation methods for pollutant removal.…”
Section: Introductionmentioning
confidence: 99%
“…(71.12 kJ/mol) . Gong et al exploited four Fe active sites on the surface of α-Fe 2 O 3 (001) to probe the impact of various activation methods and dissolved organic substances (DOM) on the energy barriers of H 2 O 2 activation to *OH (44.89 kJ/mol) . Li et al explored the dissociation of H 2 O 2 on hexagonal boron nitride and obtained seven possible species, among which the energy barrier of H 2 O 2 activation to *OH was 86.6 kcal/mol .…”
Section: Introductionmentioning
confidence: 99%
“…The OH radicals have been proven to be effective in removing many pollutants. For instance, Gong et al 25 generally investigated the effect of dissolved organic substances (DOMs) on the activation of H 2 O 2 on the surface of α-Fe 2 O 3 (001) using density functional theory, demonstrating the superior catalytic performance of its Fe site. Through the co-adsorption analysis of DOM molecules and H 2 O 2 , it was found that the active site can effectively promote the activation of H 2 O 2 to generate OH radicals, which can better oxidize DOM molecules.…”
Section: Introductionmentioning
confidence: 99%